Does the geographic clustering of universities promote their scientific research performance? Evidence from China - Shuai Chu; Mengfei Wu (Global Labor Organization (GLO), 2021)
The fundamental purpose of university geographic clustering is to gather resources through "agglomeration" to improve the performance of higher education and scientific research. However, it has been debated whether university clusters can achieve the latter goal. With the help of the “quasi-experiment” of Chinese "University Towns" project in the 1990s, this study determines the impact of university clusters on scientific research performance. Panel data of 2000 colleges and universities from 1993 to 2017 in the compilation of scientific and technical statistics of Chinese higher education and time-varying difference in differences method are used. The results show that the cluster of colleges and universities have a significant negative impact on the scientific research performance due to technological dis-proximity and rising commuting costs. And the clustering effect is related to the number of participating schools and the level of the university. Therefore, university clustering cannot effectively promote the performance of scientific research and unable to bring agglomeration economies.
Keywords: I23; O38; O53; 330; University cluster; Economies of agglomeration; Scientific research performance; Time-varying difference in differences method